Our Purchases. Where and what we buy - Lonardi, Cristina (Italian Sociological Review, 2012)
This article provides an overview of several places of consumption (stalls and markets, discount stores, specialist shops, shopping centres and new forms of purchasing) and what is bought there. In particular, it will show that the so-called cathedrals of consumption – shopping centres – are the favourite shopping destinations of today’s consumers, whose expenditure choices are irreversibly directed towards basic essentials, namely food. Indeed, this is the most substantial item of expenditure in family budgets, especially those that declare a low or medium-low socio-economic status. Albeit in a well-structured context with established forms, there is a slight increase in consumer practices linked to responsible, critical and sustainable consumption, taking shape in new forms of purchasing that differ from the traditional modes.